An Evaluating the Implementation of the Merdeka Curriculum in Teaching English in High School: Challenges and Opportunities: Evaluating the Implementation of the Merdeka Curriculum in Teaching English in High School - Aeni, Nur; NR, Nurul Masyitah; Affandi, Akhmad; A. Dzhelilov, Akhtem; Wijayanti, Tuti; Bhat, Mohd Saleem (Yayasan Corolla Education Centre, 2024)
The purpose of this study was to provide insight into how the Merdeka Curriculum is being taught at one of high school in South Sulawesi, it is SMAN 1 Takalar. Using a phenomenological descriptive design, the study gathers descriptive data from verbal or written statements as well as actions that are seen. The teachers of SMAN 1 Takalar are research participants. Based on observations, the research's conclusions showed that teachers had done a good job of implementing autonomous curriculum learning. Teachers that successfully move through the phases of learning preparation, execution, and assessment. Overall success is observed, despite difficulties in updating, and is attributed to the proactive application of distinctiveness and technology integration strategies. Teachers' assessments of the quality of learning are influenced by evaluation techniques like learning reflection. In summary, SMAN 1 Takalar's learning environment is positively impacted by the Merdeka Curriculum. encouraging dynamism and adaptability to the demands of students. In order to maximize the benefits of the curriculum and guarantee fair outcomes for all parties involved in the learning process, it is imperative that ongoing efforts be made to comprehend and address the diverse teacher viewpoints.